Geografias da ausência: paisagem, memória e experiência na prosa de Valter Hugo Mãe - PEREIRA, Renata França (2024)
The proposed dissertation addresses the novel A desumanização (2017), by Valter Hugo Mãe, from an interdisciplinary perspective, integrating contributions from geography, philosophy, sociology, psychoanalysis and literature. The work aims to explore the relationship between literary narrative and the theoretical reflections of authors such as Freud (2010), Ricoeur (2007), Halbwachs (2003), Tuan (1978; 2005; 2012; 2013; 2018) and Relph (2014), in search of a broader and deeper understanding of the complexities addressed in the work. In the context of Portuguese literature, the novel serves as a lens through which to examine fundamental themes, with landscape being a central element of analysis. Through a geographical perspective, we seek to understand how the literary construction of the landscape changes, through the eyes of the characters, in the face of a traumatic event. The philosophical approach, anchored in the contributions of Freud, Halbwachs and Ricoeur, allows for a deeper analysis of the psychological, social and symbolic dimensions present in the work. The intersection between memory and mourning, concepts explored by the authors, enriches the understanding of the narrative, offering a sociological look at the construction of the characters and their relationship with the surrounding environment. In this interdisciplinary scenario, literature acts as a medium that transcends disciplinary boundaries, allowing an enriching analysis of human complexities. By integrating Tuan and Relph's theories, we seek to understand how literary narrative dialogues with the perception and experience of space, providing insights into the way characters construct and signify their reality. In summary, the dissertation proposes an interdisciplinary approach that seeks to analyze the multiple layers of meaning present in the novel A desumanização, using the contributions of consolidated authors in their respective areas of study.